PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN, DAN PENGETAHUAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK - Isnaini Anniswati Rosyida (J-MACC, 2018)
This study aims to analyze the influence of knowledge taxation, awareness and knowledge of tax amnesty on taxpayers compliance. The population in this study is all taxpayers who perform the free work listed in the tax office Pratama North Gresik District. Variables of this study include the dependent variable (taxpayers compliance) and independent variables (knowledge taxation, awareness, and knowledge tax amnesty). This study uses primary data in the form of questionnaires. Sampling technique using random samping with slovin formula, the number of samples of 94 samples. Data analysis techniques to test the hypothesis in this study using multiple linear regression test.The results of this study show that partially knowledge of taxation have a positive and significant impact on taxpayers compliance, awareness has a positive and significant impact on taxpayers compliance, and knowledge of tax amnety have positive and significant effect to taxpayer compliance. Simultaneously knowledge of taxaxtion, awareness and knowledge of tax amnesty together have positive and significant influence to taxpayers compliance, and the most dominant independent variables is the awareness variable with beta value 0,422.